Systematic Mapping and Meta Analysis of Maize Soybean Intercropping Studies in Indonesia - Shinta Palupi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Soybean is an important food commodity in Indonesia because it is the main raw material for tofu and tempeh, two major protein sources widely consumed by the population. However, domestic soybean production remains far below national demand resulting in heavy dependence on imports. In contrast maize is increasingly preferred by farmers due to its higher productivity and a more stable economic value. Therefore, maize–soybean intercropping has emerged as a promising strategy to improve land-use efficiency while increasing soybean production without reducing maize cultivation. This study systematically mapped and synthesized maize–soybean intercropping research in Indonesia and conducted a meta-analysis of Land Equivalent Ratio LER values reported across studies. Literature searches using Scopus, Web of Science, and Google Scholar identified 179 eligible publications published between 1978 and 2023. Most studies focused on agronomic factors such as variety selection spacing arrangement and fertilizer management. Meta-analysis showed average LER values of 1.47 ± 0.046 for maize–soybean intercropping and 1.36 ± 0.081 for maize–mung bean intercropping indicating advantages over monoculture systems. However, inconsistencies in methodology and reporting standards limited study comparability and sustainability assessments. Future research should integrate ecological, social, and long-term economic indicators alongside standardized reporting frameworks to strengthen evidence-based intercropping recommendations nationally for sustainable agriculture.